Trains in crosswinds – Comparison of full-scale on-train measurements, physical model tests and CFD calculations. Issue 175 (April 2018) - Gallagher, M.; Morden, J.; Baker, C.; Soper, D.; Quinn, A.; Hemida, H.; Sterling, M.
Abstract: In this paper a major series of experiments is described that included extensive full-scale measurements of cross wind induced pressures on the Class 43 New Measurement Train over an extended 21 month period, together with wind tunnel, moving model tests and CFD calculations, and allows, for the first time, a proper evaluation of the adequacy of these techniques. Static wind tunnel tests and moving model tests show good agreement with each other, both in terms of the measured pressure field around the train and in the overall side force per unit length over the yaw angle range from 15 to 30°. Similarly the wind tunnel tests and the CFD calculations show good agreement with each other for yaw angles up to 15°. Two different analyses of the full-scale data were carried out - an analysis of 1 s average wind speeds and forces, and an analysis of specific gusts. There was a very great deal of scatter in the results and only the results from simple track topographies were found to agree well with the model and computational results. Highlights: Extensive full scale measurements of cross wind forces on trains in operational conditions. Comparison with wind tunnel, moving model rig and CFD results. Analysis of response to sudden wind gusts. Results show good comparison between methods, with large variability in full scale results.